The role of value co-creation in building trust and reputation in the digital banking era - Marcelo Royo-Vela; Moreno Frau; Alberto Ferrer (Cogent Business & Management, 2024)
This study investigates how customers co-create value in online banking. The aims of this study were twofold. First, it tests the DART model (dialogue, access, risk assessment, and transparency) as a driver of customer value co-creation. Second, this study investigates trust and reputation as the outcomes of value co-creation in online banking. Exploratory factor analysis was used by applying a Principal Components Analysis with SPSS and SMART PLS to check the model and the relationship between the factors of the DART model, value co-creation, company reputation, and customer trust. Data were collected through a questionnaire sent to 217 online bank customers. The findings show that strategic value co-creation is influenced by dialogue, access to information, risk assessment, and transparency. The results also show that customer value co-creation can result in greater reputation and trust. This study contributes to the literature in two ways. First, this study extends the marketing literature by showing that value co-creation can generate reputation and trust as an outcome, changing the perspective in which the phenomenon is traditionally observed. Second, the study tests the DART model in the online banking industry, showing that the original model also works for bank customers. This study provides managerial guidelines for each variable of the DRAT model.
Keywords: 650; Strategic value co-creation; online banking; Dart model; trust; reputation